The TAGteam motif facilitates binding of 21 sequence-specific transcription factors in the Drosophila embryo - Satija, Rahul; Bradley, Robert K.

(untitled) (Genome Research, 2012)
Highly overlapping patterns of genome-wide binding of many distinct transcription factors have been observed in worms, insects, and mammals, but the origins and consequences of this overlapping binding remain unclear. While analyzing chromatin immunoprecipitation data sets from 21 sequence-specific transcription factors active in the Drosophila embryo, we found that binding of all factors exhibits a dose-dependent relationship with “TAGteam” sequence motifs bound by the zinc finger protein Vielfaltig, also known as Zelda, a recently discovered activator of the zygotic genome. TAGteam motifs are present and well conserved in highly bound regions, and are associated with transcription factor binding even in the absence of canonical recognition motifs for these factors. Furthermore, levels of binding in promoters and enhancers of zygotically transcribed genes are correlated with RNA polymerase II occupancy and gene expression levels. Our results suggest that Vielfaltig acts as a master regulator of early development by facilitating the genome-wide establishment of overlapping patterns of binding of diverse transcription factors that drive global gene expression.